Overcoming the threat of anti-bias interventions: Combining self-report and psychophysiological measures to capture the process of change - Félice van Nunspeet; Esmee M. Veenstra; Beatriz Monteiro Graça Casquinho; Naomi Ellemers; Daan Scheepers; Miriam I. Wickham; Elena A. M. Bacchini; Jojanneke van der Toorn (PLoS ONE, 2025)
Anti-bias interventions do not always have the intended results and can even backfire. In light of research on the psychology of morality, we examined whether confronting people with evidence of their own (group’s) bias causes a (psychophysiological) threat response, and how to overcome this. We focused on an intervention addressing gender bias in teacher evaluations. After assessing their own teaching evaluations, we presented student research participants (N = 101; 71.3% female), in Part 1 of the intervention, with evidence of bias displayed in such teaching evaluations. This evidence either did (self-implied condition) or did not (self not-implied condition) include participants’ own ostensibly biased evaluations. In Part 2 of the intervention, we asked participants to reflect on the issue of gender bias, and compared the impact of two experimental instructions. In the promotion condition, instructions referred to emphasizing how the university could try to achieve the ideal of promoting fair and just evaluations of teachers. In the prevention condition, instructions referred to highlighting the university’s obligation to prevent unfair and unjust teacher evaluations. While participants verbally reflected on the intervention, during both phases (in Part 1 and Part 2) we measured their psychophysiological responses using indices of cardiovascular ‘threat vs. challenge’. Then, we used self-report measures to examine participants’ explicit responses to the different parts of the intervention. Results revealed that implicating the self in the occurrence of bias (Part 1) raises a psychophysiological threat response. However, emphasizing the future ideal of promoting fair evaluations of teachers (rather than the obligation of preventing biased evaluations; Part 2) resulted in a psychophysiological challenge response and increased perceived coping abilities to combat such bias. The implications of these findings are discussed.